Dectin-1-activated dendritic cells: A potent Th9 cell inducer for tumor immunotherapy. (1st November 2016) - Chen, Jintong; Zhao, Yinghua; Chu, Xiao; Lu, Yong; Wang, Siqing; Yi, Qing
ABSTRACT: Dendritic cell (DC)-based immunotherapy has great promise for cancer treatment. We have recently demonstrated that dectin-1-activated DCs trigger potent antitumor Th9 cells in vivo . Dectin-1-activated DC-induced antitumor responses rely on the induced Th9/IL-9. These findings offer new strategies for the development of more effective DC vaccines in tumor immunotherapy.